Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $f:\mathbb{R} \to \mathbb{R}$ be a twice differentiable function. And let $$\eqalign{ & M_0 = \sup \left|f(x)\right| \cr & M_1 = \sup \left|\frac{d}{dx} f(x) \right| \cr & M_2 = \sup \left|\frac{d^2}{dx^2} f(x) \right| \cr }$$ Prove that $$M_1 ^2 \leqslant 4M_0 M_2$$ I can not think how I can relate these values ​​in some inequality )=

share|cite|improve this question
Oh sorry , I did it <.< !! – August Oct 9 '11 at 15:21
That's great August! When that happens, it is perfectly acceptable to post your own answer below, so that others may learn how to do the problem! – Zev Chonoles Oct 9 '11 at 15:28
Oh no , sorry again , im the more stupid guy in the world <.< , what i did is wrong, sorry <.<.<<<.< – August Oct 9 '11 at 16:25
One should maybe remark here that the question implicitly assumes $M_0$ to be finite (or that $\infty\cdot 0=\infty$), because otherwise we can take $f (x)=x$, for which the inequality would read $1=M_0 \leq 4\cdot M_0 M_2= 4\cdot \infty \cdot 0$. – PhoemueX Jan 7 '15 at 17:47
@PhoemueX: not only, we also have to assume that $f''$ is not identically zero, otherwise for $f(x)=ax+b$ on $(0,1)$ the inequality states $a^2\leq 0$. – Jack D'Aurizio Jan 12 '15 at 20:46
up vote 5 down vote accepted

This is an exercise in Rudin's Principles of Mathematical Analysis, if I remember correctly, where it appears with a generous hint. I think the solution alluded to runs as follows.

Fix $x\in\mathbb R$. For $h>0$, you can expand $f(x+2h)$ via Taylor's theorem: $$ f(x+2h) = f(x)+f'(x)2h+\frac{f''(\xi)}{2!}(2h)^2 $$ where $\xi\in(x,x+2h)$. So $$ f'(x)=\frac{1}{2h}\left[f(x+2h)-f(x)\right]-f''(\xi)h $$ From here you can bound $|f'(x)|$: $$ |f'(x)|\leq\frac{1}{2h}|f(x+2h)-f(x)|+|f''(\xi)|h\leq\frac{M_0}{h}+M_2h. $$ Since $x$ is arbitrary, you can replace $|f'(x)|$ with $M_1$. If $M_2=0$, let $h\to\infty$ to get $M_1=0$. Otherwise, rearrange to get $$ 0\leq M_2h^2-M_1h+M_0=M_2\left(h-\frac{M_1}{2M_2}\right)^2+\frac{4M_2M_0-M_1^2}{4M_2}. $$ Take $h=\frac{M_1}{2M_2}$ to get the inequality.

share|cite|improve this answer
Remark: we must assume $M_2>0$, since the inequality does not hold for linear functions. Given that, we can just take $h=\sqrt{\frac{M_0}{M_2}}$ in the bound for $|f'(x)|$. – Jack D'Aurizio Jan 12 '15 at 21:01
@JackD'Aurizio Well I guess I tacitly assumed that $M_0<\infty$, in which case $M_2=0$ forces $M_1=0$ as the argument shows (and if $M_2>0$ we could just take $h=\sqrt{M_0/M_2}$ as you say, avoiding the algebraic step at the end). But I agree that if we allow $M_0=\infty$ then the inequality won't make sense as stated for $M_2=0$. – Nick Strehlke Jan 12 '15 at 21:17

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.